Unraveling the in vitro secretome of the phytopathogen Botrytis cinerea to understand the interaction with its hosts - González-Fernández, Raquel; Valero-Galván, José; Gómez-Gálvez, Francisco J.; Jorrín-Novo, Jesús V. (Frontiers in Plant Science, 2015)
Botrytis cinerea is a necrotrophic fungus with high adaptability to different environments and hosts. It secretes a large number of extracellular proteins, which favor plant tissue penetration and colonization, thus contributing to virulence. Secretomics is a proteomics sub-discipline which study the secreted proteins and their secretion mechanisms, so-called secretome. By using proteomics as experimental approach, many secreted proteins by B. cinerea have been identified from in vitro experiments, and belonging to different functional categories: (i) cell wall-degrading enzymes such as pectinesterases and endo-polygalacturonases; (ii) proteases involved in host protein degradation such as an aspartic protease; (iii) proteins related to the oxidative burst such as glyoxal oxidase; (iv) proteins which may induce the plant hypersensitive response such as a cerato-platanin domain-containing protein; and (v) proteins related to production and secretion of toxins such as malate dehydrogenase. In this mini-review, we made an overview of the proteomics contribution to the study and knowledge of the B. cinerea extracellular secreted proteins based on our current work carried out from in vitro experiments, and recent published papers both in vitro and in planta studies on this fungi. We hypothesize on the putative functions of these secreted proteins, and their connection to the biology of the B. cinerea interaction with its hosts.